Reactive and inelastic scattering probabilities for the Cl+H2 scattering - Gogtas, F; Akpinar, S; Bulut, N (Elsevier Science Bv, 2004)
In this paper, three-dimensional Cl + H-2(v,j) --> ClH(v',j') + H and Cl + H-2(v,j) --> Cl + H-2(v',j') reactions at zero total angular momentum have been studied by using a time-dependent quantum wave packet method. Reactive and inelastic scattering probabilities for a broad range of energy are calculated. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: inelastic scattering; reactive scattering; wavepacket study